CONDOM USE AMONG EXIT CLIENTS OF FEMALE SEXUAL WORKERS FOR PREVENTION HIV/AIDS IN MAKASSAR - M. Akbar Alwi; Yusdalia Yusdalia (UNEJ e-Proceeding)
AIDS remains a public health problem of majorsignificance in most parts of the world [1]. Accordingto United AIDS Nation program on HIV/AIDS(UNAIDS) global report published for the world AIDSday 2012, about 34 (31,4-35,9) million people areliving with HIV[2]. Based on the data fromDirectorate General CDC & Ministry of Health, in2014 the number of cases HIV and AIDS in Indonesiawas 7.335 and 176 respectively. The most mode oftransmission is heterosexual. There were 34.305cases with the mode[3]. Data from AIDS CommissionMakassar showed that in 2013, the number of HIVcases in Makassar was 3.845 and AIDS 1.673 cases.According to the data, Makassar ranked first in thenumber of cases of HIV/AIDS in South SulawesiprovinceClients of female sexual workers (FSWs) have risk tobe attacked by HIV. The clients (FSWs), also knownas the “bridge population”, act as a bridge betweenthe high risk group of FSWs and the generalpopulation [4] .The higher number of clients of FSWs,the higher spread of HIV/AIDS both in high risk groupand general population. Low condom use is triggerof HIV/AIDS transmission. In 2014, rapid surveyresult on FSWs in Makassar showed that condomuse has not reached yet 100%. Makassar AIDScommission has conducted regularly socializationHIV/AIDS to FSWs and approached to them, in orderto insist male clients to use condom. But, condomuse in male clients has not been maximal. Thissurvey was carried out to know characteristic exitclients and determinant factors of condom. Theresult of survey can be used as reference to crateplanning in controlling HIV/AIDS in Makassar.